European product liability : an analysis of the state of the art in the era of new technologies - Machnikowski, Piotr, editor; European Group on Tort Law. (Cambridge : Intersentia, 2016)
Thirty years after the entry into force of the Directive on liability for defective products (Council Directive 85/374/EEC), and in the light of the threat to user safety posed by consumer goods that make use of new technologies, it is essential to assess and determine whether the Directive remains an adequate legal response to the phenomenon of products brought to market that fail to ensure appropriate levels of safety for their users. European Product Liability is the result of an extensive international research project funded by the Polish National Science Centre. It brings together experienced scholars associated with the European Group on Tort Law (EGTL) and the European Research Group on Existing EC Private Law (Acquis Group). Individual country reports analyse the implementation of the Directive in the domestic law of several EU and EEA Member States (namely Austria, Czech Republic, Denmark, England, France, Germany, Italy, Netherlands, Norway, Poland, Spain, and Switzerland) and the relationship of the implemented rules with the already existing rules of tort law. The country reports show that the practical significance of product liability differs widely in the various Member States. Also taking into account non-EU countries (Canada, Israel, South Africa and the USA), this book examines whether EU law will ensure sufficient safety for individuals using goods that have been produced using new technologies that are currently under development, such as major advances in mechatronics, nanotechnology, regenerative medicine and contour crafting. Together with an economic analysis of product liability it makes the book valuable for academics, practitioners, policy makers and all those interested in the subject.
"European Group on Tort Law"--Cover.
"Acquis Group"--Cover.
Includes bibliographical references.
Keywords: Products liability -- Europe; Products liability; consumentenrecht; productenaansprakelijkheid; Europa; 86.67 consumer law; Europe